Peningkatan Kompetensi Guru Madrasah Ibtidaiyah melalui Pelatihan Pembuatan Media Pembelajaran Kreatif di Kota Lhokseumawe - Fazilla, Sarah; Safitri, Maya; Fauziana, Fauziana; Subarja, Putri Ananda (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2023)
This study focuses on enhancing the skills of Madrasah Ibtidaiyah teachers in Lhokseumawe in the creation of creative learning media. The training aims to improve and elevate the practices of media creation, which have been considered simplistic and uneven across different teaching materials. The approach used is action research. The study was conducted in two sessions on January 20-21, 2022. The research method includes a cycle of planning, action, observation, and reflection. Data collection techniques involved interviews, observations, and documentation. The results of this action research demonstrate that the training, attended by 20 participants, was successful in improving their practical skills in creating creative learning media. However, participants felt that the duration of the training was too short and expressed a desire for more in-depth material and longer discussion sessions. The evaluation also showed general satisfaction with the material and facilitators. The implications of this research indicate the need for developing a continuous training program with a more flexible schedule and more comprehensive material. Increasing the allocation of time for discussion and practice should also be considered. The goal is to enhance the effectiveness of future training, focusing on improving the quality of learning media and the skills of teachers in creating more innovative teaching materials that meet the needs of Madrasah Ibtidaiyah education.